ONLINE AND OFFLINE LEARNING: COMPARATIVE ANALYSIS AND PROSPECTS - Jabborova Dildora Bobirqizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article is about learning and offline learning in the education system today. It looks at how they work what is good about them and what is not so good. With new digital tools coming out all the time online learning is getting more popular because it is flexible and people can get to it from anywhere. Online learning also has ways of teaching that can make learning better. However online learning has some problems like not being able to talk to people in person having trouble with technology and needing to be self-disciplined. On the hand offline learning or traditional learning is good because it has a set schedule people can talk to each other and students can interact with another. Offline learning is not flexible and it does not use a lot of technology.The study also looks at something called learning or hybrid education, which is a mix of online learning and offline learning. It takes the things from online learning and offline learning and puts them together. The study says that online learning and offline learning are both good but they can be even better if they are used together. This can make education better, for everyone make people more interested and help people learn more.